Talk as Action: A Narrative Approach to Action Theory - Arvay, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2007)
Explains the contribution narrative makes to counselors' understanding of human action. By viewing action from a narrative perspective, it extends the construct of action beyond the realm of goal-directed behavior into the realm of language. States counselors must pay attention to the ways language can affect therapeutic practices.